Repellency of the different crude extracts of Epichloë bromicola from Elymus tangutorum and enzyme activities in Tribolium castaneum Herbst. Issue 1 (June 2021) - Ren, Ting; Li, Fan; Shi, Qian; Cheng, Fang-Shu; Guo, Zhao-Ling; Song, Qiu-Yan; Guo, Chao
Abstract: The study was to determine the repellency of crude extracts of Epichloë bromicola at different altitudes against Tribolium castaneum Herbst, and the effect of crude extracts of endophytic fungi with higher repellent activity on superoxide dismutase, catalase and cytochrome P450. The percent repellency and the activities of three enzymes were measured at the concentration of 0.25mg/mL after 2h and 4h with different crude extracts. The correlation between altitude and avoidance rate was analyzed. The stain 1, 6, and 9 at the maximum concentration of 2.5mg/mL had better repellency (66%, 59%, and 65%, respectively). The concentrations of 0.25mg/mL treatment had a higher rate of avoidance, so this concentration was selected and the enzyme activity was determined. The activities of SOD, CAT, and CYP450 were significantly increased by three crude extracts of Epichloë bromicola compared with the control.